Peran Intensitas Modal dan Tingkat Hutang terhadap Agresivitas Pajak - Eka Putri Julianti Wibowo; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
This study is intended to find out and provide tangible evidence of the influence of Capital Intensity and Debt Level on Tax Aggressiveness in Property and Real Estate companies listed on the Indonesia Stock Exchange. This observation uses Tax Aggressiveness as the dependent variable and Capital Intensity and Debt Level as independent variables. This study uses a quantitative descriptive approach. The sample in this observation uses a purposive sampling method using financial report data for 5 years, and journals that have been researched by the researchers. The type of data for this research is secondary data obtained from the analysis of financial report data, international journals, national journals, astikels, and books. This hypothesis was tested using descriptive statistical analysis, classical assumption tests, multiple regression tests and hypothesis tests, namely the r analysis test and the t test. The results of this study show that Capital Intensity and Debt Level have a significant positive impact on Tax Aggressiveness.